2022
DOI: 10.3389/fbioe.2022.997243
|View full text |Cite
|
Sign up to set email alerts
|

Advances in biomaterials as a retinal patch for the repair of rhegmatogenous retinal detachment

Abstract: Rhegmatogenous retinal detachment (RRD) is the most common retinological emergency that can cause blindness without surgical treatment. RRD occurs when liquefied vitreous accumulates between the neurosensory retina and the retinal pigment epithelium via retinal breaks, which are caused by the separation of the vitreous from the retina with aging. Currently, the main treatment option is pars plana vitrectomy, which involves surgical removal of the vitreous and laser photocoagulation around retinal breaks to gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…Therefore, the exosome engineering strategy may greatly help treat clinical osteoarthritis in the future. [187] In addition to the direct genetic modifications of parental cells to obtain EVs that express multiple nucleic acids, appropriate regulation of the culture conditions of parental cells can also enhance the overexpression of certain miRNAs targeting bone and cartilage regeneration, resulting in biological effects similar to those of cell transfection. Shen et al performed the hypoxic preconditioning of BMSCs.…”
Section: Endogenous Modificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the exosome engineering strategy may greatly help treat clinical osteoarthritis in the future. [187] In addition to the direct genetic modifications of parental cells to obtain EVs that express multiple nucleic acids, appropriate regulation of the culture conditions of parental cells can also enhance the overexpression of certain miRNAs targeting bone and cartilage regeneration, resulting in biological effects similar to those of cell transfection. Shen et al performed the hypoxic preconditioning of BMSCs.…”
Section: Endogenous Modificationmentioning
confidence: 99%
“…used miR‐212‐5p mimics to transfect synovial MSCs and detected the upregulation of miR‐212‐5p expression in secreted exosomes. [ 187 ] Further experiments showed that the miR‐212‐5p‐overexpressed exosomes significantly inhibited IL‐1β‐induced chondrocyte degeneration and inflammatory response, and excessive chondrocyte degeneration and inflammation are often the representative pathological manifestations of osteoarthritis. Therefore, the exosome engineering strategy may greatly help treat clinical osteoarthritis in the future.…”
Section: Micro‐modification Of Evs: Engineered Evs To Promote the Rep...mentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo investigation with fibrin hydrogels revealed high short-term subretinal biocompatibility of this type of DDS, which is a suitable scaffold for human Embryonic Stem Cell- Derived Retinal Pigment Epithelial Cells (hESC-RPE) transplantation, which could be a new grafting material for tissue engineering RPE cells [ 206 ]. A small series of rhegmatogenous retinal detachment models with short-term follow-up provide preliminary evidence to support the favorable biocompatibility and efficacy of the hyaluronic acid (HA) hydrogel as a promising retinal patch for sealing retinal breaks in retinal detachment repair [ 207 ]. Moreover, gene delivery using an injectable hydrogel has also been studied as a treatment for retinitis pigmentosa [ 208 , 209 ].…”
Section: Innovative Drug Delivery Systemsmentioning
confidence: 99%
“…Despite the technical advances in retinal surgery, RRD is considered a sight-threatening condition and must be treated as quickly as possible [2][3][4]. Additionally, after having achieved a good anatomical retinal reattachment, the postoperative visual acuity (VA) gain is often incomplete in many subjects [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%